Divine Roots: The Etymology of Thoth - Cooper, Julien Charles 19XX- (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The names of gods are an important expression of the Egyptian experience of the divine. Understanding the etymology of divine names can give us insights into the conceptions of the oldest adherents of religious cults, allowing us to appreciate of the essence of the original deity. This analysis will propose an etymology for the name of the god Thoth and situate the god’s name in its proper lexical and theological context, relating the divine name Ḏḥw.ty to an Old Egyptian root for ‘bright’ or ‘white’ and thus lunar concepts. This etymology not only satisfactorily explains the lexical root and theology of Thoth but is also consistent with other patterns in Egyptian divine epithets and names. Using cognates from Afroasiatic languages, the analysis proves that there once existed an ancient lexical root ḏḥ(w) in Old Egyptian or ‘Pre-Old Egyptian’. This root also explains various other nouns in Egyptian such as a type of linen ( ḏḥ ), the metallic substances of tin ( ḏḥ ) and lead ( ḏḥ.ty ), as well as a word for ‘teeth’ ( nḏḥ.yt ). This analysis demonstrates that some gods’ names are to be found in lexical roots which become unproductive in later stages of the Egyptian lexicon.